Evaluation of Factors of Low Birth Weight Deliveries: A Cross Sectional Study - Karki, Shrijana; Shakya, Vivechana (Journal of Nepal Health Research Council, 2022)
Background: Low birth weight is the most serious challenge for infant survival, healthy growth and development. It is the major determinant of the infant morbidity, mortality and disability in childhood. Different maternal and newborn factors contribute to Low birth weight. Hence, this study aims to assess the factors of low birth weight among deliveries at a tertiary hospital.Methods: A cross sectional analytical study was conducted among 203 postnatal mothers who had delivered low birth weight babies in Patan hospital from 1st September to 30th November 2019.Purposive sampling technique was used to select the sample for the study. Interview was conducted using a self-structured questionnaire. Data were analyzed with SPSS version 20 using descriptive and independent sample t-test to identify factors of Low birth weight.Results: Increased amount of dietary intake, consumption of folic acid tablet, iron and folic acid tablet (p<0.01,CI:95%), calcium tablet(p<0.05) and hypertension during pregnancy(p<0.01) can make significant differences in the mean birth weight of the baby. Similar difference was observed with the sex of baby (p=0.05)and gestational age at birth(p<0.01).Conclusions: Less dietary intake and micronutrients supplements are largely responsible for the Low birth weight. Possible maternal factors can be eliminated in order to reduce Low birth weight deliveries. Therefore, emphasis should be given on these factors while providing antenatal care via health teaching and counseling to mothers.Keywords: Factors of low birth weight; postnatal mothers; tertiary hospital.